2021
DOI: 10.2166/aqua.2021.100
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' purchasing intentions for efficient water-saving products: the mediating effects of altruistic and egoistic values

Abstract: Efficient water-saving appliances are an essential part of changing water consumption toward a more sustainable future. Unlike previous studies, this research focuses on egoistic and altruistic values as determinants of consumers' willingness to buy efficient water-saving appliances. In this study, a convenient sampling technique was used to solicit data from 308 potential consumers. Using a two-steps structural equation model method for data analysis, the results show that both egoistic and altruistic values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Individuals with egoistic concerns take care of their own welfare. Sarpong et al [58] showed that egoistic and altruistic environmental concerns were positive drivers of consumer willingness to purchase efficient, water-saving appliances. Aprile and Fiorillo [59] showed that there is a positive correlation between egoistic environmental concerns and water conservation behavior when general environmental issues are perceived as a threat to one's own welfare.…”
Section: Hypothesis 2 (H2)mentioning
confidence: 99%
“…Individuals with egoistic concerns take care of their own welfare. Sarpong et al [58] showed that egoistic and altruistic environmental concerns were positive drivers of consumer willingness to purchase efficient, water-saving appliances. Aprile and Fiorillo [59] showed that there is a positive correlation between egoistic environmental concerns and water conservation behavior when general environmental issues are perceived as a threat to one's own welfare.…”
Section: Hypothesis 2 (H2)mentioning
confidence: 99%
“…For this investigation, the study adopted the convenience sampling and targeted the Chinese people for empirical model investigation. In the findings, the study illustrated significant and positive results for the derived relationships and the results supported the altruistic and ecological values of green products as a supportive positive mediator in increasing the customers intentions to use the water saving efficient appliances that have an environmental reserving concept (Sarpong et al, 2021). Thus, with the help of these mentioned studies, the researcher found enough empirical evidence to investigate the altruistic values as a mediator and can cast a catalytic effect for stimulating the customer intentions to use green packaged products.…”
Section: H3: Symbolic Value Strongly Mediates the Relationship Betwee...mentioning
confidence: 52%
“…The research provides policy suggestion and found the vital role of altruistic warmth in the domain of sustainable consumer behavior among communities (Song & Kim, 2019). Therefore, the studies from past have suggested that: H7: Altruistic Value mediates the relationship between Consumption Functionality and Product meaningfulness A recent study (Sarpong et al, 2021) investigated the mediating role of the altruistic values of the customers in between the consumers environmental attitude and their willingness to buy and use the water saving efficient appliances. For this investigation, the study adopted the convenience sampling and targeted the Chinese people for empirical model investigation.…”
Section: H3: Symbolic Value Strongly Mediates the Relationship Betwee...mentioning
confidence: 98%
“…This approach is particularly suited to the study's objectives, which aim to elucidate the complex relationships between various consumer behaviors and sustainability attributes in craft beer consumption. The questionnaire, developed with reference to established frameworks by Sarpong et al (2021) and Sharma (2022), ensures a comprehensive exploration of consumption habits, environmental concerns and attitudes related to water usage, carbon footprint, organic farming and local sourcing, to craft beer purchase intentions. The incorporation of multiple blocks within the instrument facilitated rotation between constructs and items within each construct to avoid bias.…”
Section: Methodsmentioning
confidence: 99%